Rift Valley fever virus outbreak in Mauritania yet again in 2022: No room for complacency - Shehroze Tabassum; Farhan Naeem; Masood Azhar; Aroma Naeem; Malik O. Oduoye; Tirth Dave (Health Science Reports, 2023)
Abstract Rift Valley fever is an important yet ignored viral hemorrhagic fever claiming many lives of African and Arabian countries over the past decade. Unfortunately, a recent outbreak of Rift Valley fever is currently ravaging in Mauritania. Death toll is rising continuously with 23 deaths reported in the month of October, 2022. Our article aims to shed light on the ongoing Rift Valley fever outbreak and recommendations to eradicate this potential threat to public health. Online databases including PubMed, the Lancet, and Science Direct as well as conferences, news, and press releases were used to for data collection. All the available medical literature related to Rift Valley fever in Mauritania were taken into consideration while writing the manuscript. As of October 17, 2022, 47 cases have been documented out of which 23 are dead. Case fatality rate has been reached to 49% which has given a wakeup call to the authorities. Efforts are being made by the concerned authorities and World Health Organization to halt the progression of this outbreak. Further investigations are required to completely eradicate the recurrent outbreaks in Mauritania especially in the area of vaccine development. Active involvement of public with the government authorities is of extreme significance in combating this disease.